Medicine of Words: Purgative Reading in Richard Rolle’s Meditations on the Passion - McCann, D (Brepols, 2015)
This article explores the idea of therapeutic reading during the later Middle Ages in relation to Richard Rolle’s Meditation on the Passion. Focusing on Rolle and his therapeutic conception of reading as a medicine of words, the article begins by noting the great frequency with which medical terms, images, and phrases occur in his vernacular writings. It highlights how sin is understood by Rolle as an affective poison, one that must be removed from the soul through intense affective states that are held to be purgative. The article then moves to consider how exactly medieval texts evoke affective states. It notes the importance of vivid images and their ability to elicit emotive responses, but then turns to medieval texts on grammar and the art of poetry for new ways of understanding precisely how words can evoke the passions of the soul. The article then offers a close reading of Rolle’s Meditation on the Passion in light of these grammatical texts, and demonstrates how it functions as a medicine of words — as a texts that works to purge the soul of sin through intense affect states.